English phonetics and phonology - Roach, Peter (Cambridge University Press, 2000)
Recognised as the most practical and comprehensive text in the field of phonetics, this third edition of English Phonetics and Phonology includes revised transcriptions, a wider discussion of different varieties of English and an updated treatment of intonation